ETIKA BELAJAR MENGAJAR DALAM PROGRAM FIELD STUDY DI FAKULTAS USHULUDDIN UIN SUNAN KALIJAGA YOGJAKARTA - Andriyani, Andriyani; Ahmad Arifi; Indal Abror (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Teaching and learning ethics include moral values, professionalism, responsibility and commitment in the educational process. The Field Study program is a learning method that allows students to learn directly in the field, applying the theory learned in class to real situations. This program provides a different learning experience and broadens students' horizons through direct interaction with the surrounding environment. The research method used in this research is descriptive qualitative research. Informal research in this research is one of the field study students. The data collection techniques used by researchers are through observation, interviews and documentation. Apart from that, this research also uses data validity testing through source triangulation and technical triangulation. Data analysis through data collection, data reduction, data presentation, and drawing conclusions. Results and discussion, (1), General description of teaching and learning ethics. (2), Implementation of teaching and learning ethics in the Field Study program. (3), Challenges faced in implementing teaching and learning ethics.